Mathematical Model for Traffic Flow - C, Keerthika; Greeshma, Narahari; Vyshnavi, Priya; Kumar Reddy, Vyshnavi; Indhira, K.; M. Chandrasekaran, V. (International Journal of Engineering and Technology, 2018)
Every year countless hours are lost in traffic jams. When the density of traffic is sufficiently high small disturbances in vehicleâ€™s accelerations can cause phantom traffic jams. We can relate the traffic flow to mathematics and physics like that of liquids and gases. This paper presents mathematical model for phantom jams and Gauss Jordan elimination for traffic flow.Â Â